Strategi Pengabdian melalui Edukasi Inovasi Makanan Pepaya untuk Mendorong Pertumbuhan UMKM di Desa Naga Kesiangan Kecamatan Tebing Tinggi Kabupaten Serdang Bedagai - Alif Alfito Ritonga; Widiya Wulandari; Aulia Fitri Rahmi; Nur Indah Septiyani Sirait; Siti Aisyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The community service program through the Real Work Lecture (KKN) aims to empower Micro, Small, and Medium Enterprises (MSMEs) in Naga Kesiangan Village, Tebing Tinggi District, Serdang Bedagai Regency, through education on papaya processing innovations as an effort to strengthen the local economy. This village has abundant papaya production potential, but its utilization is still limited to selling fresh fruit, so that the economic added value is not optimal. The program implementation method uses a participatory approach that includes field observations, focus group discussions, training and demonstrations of papaya processing, packaging and branding assistance, and evaluation of activity results. The training focused on making processed papaya products such as dodol, chips, and jam, accompanied by strengthening knowledge of business management and simple marketing. The results of the activity showed an increase in community knowledge and skills in processing papaya into value-added products, increased interest in entrepreneurship, and the formation of papaya-based business groups as a step to program sustainability. The resulting processed products have a higher selling value than fresh papaya and have the potential to increase household income. This program contributes to strengthening the capacity of MSMEs, encouraging the utilization of local potential, and supporting sustainable village economic development.